Hard ticks (Ixodida: Ixodidae) in the Colombian Caribbean harbor the Jingmen tick virus: an emerging arbovirus of public health concern (2024)
Background Ticks are obligate hematophagous ectoparasites involved in transmitting viruses of public health importance. The objective of this work was to identify the Jingmen tick virus in hard ticks from the Colombian Carib‑ bean, an arbovirus of importance for public health. Methods Ticks were collected in rural areas of Córdoba and Cesar, Colombia. Taxonomic identification of ticks was carried out, and pools of 13 individuals were formed. RNA extraction was performed. Library preparation was per‑ formed with the MGIEasy kit, and next-generation sequencing (NGS) with MGI equipment. Bioinformatic analyses and taxonomic assignments were performed using the Galaxy platform, and phylogenetic analyses were done using IQ-TREE2. Results A total of 766 ticks were collected, of which 87.33% (669/766) were Rhipicephalus microplus, 5.4% (42/766) Dermacentor nitens, 4.2% (32/766) Rhipicephalus linnaei, and 3.0% (23/766) Amblyomma dissimile. Complete and partial segments 1, 2, 3, and 4 of Jingmen tick virus (JMTV) were detected in the metatranscriptome of the spe‑ cies R. microplus, D. nitens, and A. dissimile. The JMTVs detected are phylogenetically related to JMTVs detected in Aedes albopictus in France, JMTVs detected in R. microplus in Trinidad and Tobago, JMTVs in R. microplus and A. variegatum in the French Antilles, and JMTVs detected in R. microplus in Colombia. Interestingly, our sequences clustered closely with JMTV detected in humans from Kosovo. Conclusions JMTV was detected in R. microplus, D. nitens, and A. dissimile. JMTV could pose a risk to humans. There‑ fore, it is vital to establish epidemiological surveillance measures to better understand the possible role of JMTV in tropical diseases.